Architecture of a distal pre‐vegetation braidplain: Cambrian middle member of the Wood Canyon Formation, southern Marble Mountains, California, USA - Muhlbauer, Jason G.; Fedo, Christopher M.; Moersch, Jeffrey E.; Bristow, Charlie (Sedimentology, 2020)
Architectural element analysis and detailed mapping of a 300 m along‐strike exposure of the middle member Wood Canyon Formation, southern Marble Mountains, California, USA, provides new evidence for extensive braided–fluvial channel‐belt deposits with adjacent overbank environments. Three‐dimensional models constructed using ‘Structure from Motion’ techniques, combined with field‐based observations, allowed interpretation of outcrop‐scale trends, barforms, channel fills and fine‐scale features. The ca 80 m thick member is divisible into five distinct units, including units M1 to M3 that form the bulk of the stratigraphy. Units are defined by stacking patterns of three facies associations (Facies Association 1 to Facies Association 3), each representing the product of a subenvironment within the fluvial system. In Facies Association 1, stacked cosets, interpreted as low‐relief fluvial bars and channel fills, preserve vertical‐accretion and downstream‐accretion elements under unimodal north‐north‐west palaeoflow, with minor lateral accretion near bar edges. Deposits of Facies Association 2 to Facies Association 3, linked to overbank environments, are found only in unit M2, in the middle 27 m of the middle member. Floodplains, represented by Facies Association 2, include crumbly red‐orange intervals of fine to medium‐grained sandstone and thinner sets of cross‐bedding than Facies Association 1, interbedded with thicker cross‐stratification indicative of overbank splay or overland flow aggradation from adjacent channel belts during flood stage. Possible aeolian beds of Facies Association 3 preserve broad festooned trough cross‐strata that average 23 cm in thickness; their small size, medium‐grained sandstone and iron oxide cement suggest a high water table. The diverse assemblage of interpreted subenvironments, paired with bedform and facies patterns, implies a perennial fluvial system that gradually built large sand bars as the channel belt migrated and avulsed across an unconfined braided–fluvial reach, leaving the overbank area on its flanks subject to weathering and aeolian transport. Despite the occurrence of strata deposited in low‐energy and ponded settings, and a marine influence proposed for nearby sections of middle member, no ichnofossils were encountered.